Impact of Ethnic Civil Conflict on Migration of Skilled Labor - Julie Christensen; Darius Onul; Prakarsh Singh (Institute for the Study of Labor (IZA), 2016)
We reevaluate the hypothesis and empirical result that ethnic civil wars lead to higher skilled emigration (Bang and Mitra, 2013). We develop a simple conceptual framework that predicts contrasting results depending upon if the economy is assumed to be agglomerating in skilled labor or non-agglomerating with network effects. In the latter case, non-ethnic wars may lead to higher skilled emigration. A regression model that accounts for the time-varying definition of migration and includes important explanatory variables shows that non-ethnic wars as opposed to ethnic wars may lead to more skilled emigration.
Keywords: J1; F2; O1; 330; civil war; emigration; brain drain; ethnic war; agglomeration; high-skilled migration